A PHENOMENOGRAPHIC STUDY ON EFL TEACHERS’ CONCEPTIONS OF TEACHING WRITING - Gebrekidan, Habtamu; Zeru, Assefa (Universitas Islam Sumatera Utara (UISU), 2024)
Teachers’ conceptions and approaches to teaching have stronger influence on students’ learning orientations and learning outcomes. This research aimed at examining English as a Foreign Language (EFL) teachers’ conceptions of teaching writing by adopting qualitative research design with interpretative ontological and epistemological assertions. To this end, 16 EFL teachers working at Wollo University, Dessie Campus were involved in semi-structured interviews arranged to explore the different ways that EFL teachers understand teaching writing. The interviews transcribed verbatim and analyzed using phenomenographic data analysis scheme. As the results of the study revealed, six qualitatively different conceptions of teaching writing were identified: (1) awareness-raising, (2) equipping, (3) mimicking, (4) co-writing, (5) practicing, and (6) inspiring conceptions of teaching writing. Three dimensions of variation such as conceptions of writing, locus of teaching writing and beliefs in acquisition of writing skills were discovered to show hierarchical relationships among the categories from simplistic (surface) conceptions of teaching to sophisticated (deep) conceptions of teaching writing. Accordingly, inclusiveness and complexity of teaching conceptions increased as we moved from Category 1 to Category 6. Equipping and practicing conceptions were found to be the most frequently reported conceptions of teaching writing, but institutional and contextual factors adversely impacted the feasibility of practicing conceptions of teaching in EFL writing classes. The findings generally revealed EFL teachers’ tendency to surface conceptions of teaching writing. The study have implications to depict teachers’ orientation to create educational environments that foster deep conceptions and approaches to teaching and learning writing skills at Ethiopian universities.